The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2016
DOI: 10.55453/rjmm.2016.119.3.5
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors and quality of life in late-life depressive disorders

Abstract: Late-life major depression is a high-incidence and difficult-to-treat affective disorder. Diagnosis of major depression in old age could also could be a challenge, due to aspects like (1) there is a higher vulnerability to the stigma of depression in this population, (2) hypochondriac ideation and somatic symptoms are the main symptoms, while depressive disposition or anhedonia are under-reported by such patients, (3) differential diagnosis includes various organic diseases, but also severa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 0 publications
0
18
0
Order By: Relevance
“…The vast majority of the existing antipsychotics are associated with adverse metabolic effects, and switching from the currently administered agent to a metabolically more favourable one is not always possible or even recommended ( 19 ). In addition, monotherapy is rarely used in clinical practice in patients with severe mental disorders, and other pharmacological agents (mood stabilizers, antidepressants and sedatives) used as add-ons may further complicate the adverse events profile ( 20 ).…”
Section: Metabolic Dysfunctions In Patients Undergoing Antipsychotic ...mentioning
confidence: 99%
“…The vast majority of the existing antipsychotics are associated with adverse metabolic effects, and switching from the currently administered agent to a metabolically more favourable one is not always possible or even recommended ( 19 ). In addition, monotherapy is rarely used in clinical practice in patients with severe mental disorders, and other pharmacological agents (mood stabilizers, antidepressants and sedatives) used as add-ons may further complicate the adverse events profile ( 20 ).…”
Section: Metabolic Dysfunctions In Patients Undergoing Antipsychotic ...mentioning
confidence: 99%
“…Diana Vetter 1 , Nicolas Salvetat 1 , Francisco Checa Robles 1 , Christopher Cayzac 1 , Jacques Dainat 1 , Benjamin Dubuc 1 , Aurélie Delacretaz 2 , Vincent Masetti 2 , Franziska Gamma 2 , Jean-Philippe Lang 3 , Dinah Weissman 1,* 1 ALCEDIAG, 2 Les Toises, 3 Les Toises, ALCEDIAG Introduction: In clinical practice, differentiating bipolar disorder (BD) from unipolar depression is challenging due to the depressive symptoms, which are the core presentations of both disorders.…”
Section: Mdd From Bipolar Depression In Patientsmentioning
confidence: 99%
“…Yuichi Esaki 1,* , Kenji Obayashi 2 , Keigo Saeki 2 , Kiyoshi Fujita 1 , Nakao Iwata 3 , Tsuyoshi Kitajima 3 1 Okehazama Hospital, 2 Nara Medical University School of Medicine, 3 Fujita Health University School of Medicine Introduction: A previous cross-sectional study reported that nighttime light is associated with increased occurrence of manic symptoms in bipolar disorder; however, the longitudinal association between nighttime light and subsequent mood episode relapses remains unclear. We determined whether bedroom nighttime light was associated with mood episode relapses in patients with bipolar disorder.…”
Section: P59 | Effect Of Nighttime Bedroom Light Exposure On Mood Epi...mentioning
confidence: 99%
“…Combining multiple antidepressants or adding different agents to the ongoing antidepressant in order to improve its efficacy or to speed its onset is not without risks, and adverse events might appear more often in these patients, especially in vulnerable populations (i.e., patients with late-life depression, multiple somatic or psychiatric comorbidities, etc.) [ 3 , 4 , 5 , 6 , 7 ]. The risk of negative pharmacokinetic and pharmacodynamic interactions also needs to be considered when multiple medications are concomitantly administered in patients with MDD, potentially triggering more frequent treatment tolerability and tolerance problems than in the case of monotherapy [ 5 , 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%